Online Learning to Foster Discipline Character (Qualitative-Phenomenological Study at SMKN 8 Malang) - Muhammad Odik Afifin (Universitas Veteran Bangun Nusantara, 2022)
In the current condition of face-to-face learning activities in the classroom, teachers and parents are encouraged to work together to continue to be able to facilitate students in learning to develop academic knowledge and personality as in previous conventional schools. This study intends to describe and explain the application of online learning that fosters disciplined character in SMK Negeri 8 Malang. This study uses a qualitative approach to the theoretical material of phenomenology. Data were collected using in-depth interviews, observation and documentation techniques. Informants were selected using a purposive technique combined with a snowball sampling technique. Through this research, the following findings were obtained: The implementation of distance learning applied at SMK Negeri 8 Malang consists of 3 approaches, namely Online learning, Offline learning or P2P and Learning mixed system. The implication of this research is to examine online learning that fosters disciplined character in SMK Negeri 8 Malang. The data obtained from the field are analyzed, thus providing several conclusions as well as enriching the study of the development of learning technology, especially about distance learning (online and offline) in the implementation of online learning that fosters a disciplined character.